Descripción del macho de Bistriopelma matuskai Kaderka 2015 y de una nueva especie de Bistriopelma de Perú (Araneae: Theraphosidae: Theraphosinae) - Kaderka, Radan (2017)
The male of Bistriopelma matuskai Kaderka 2015 is described and illustrated, the species is rediagnosed and complemented by new biogeographical data. Additionally, a new species of Bistriopelma, B. titicaca sp. nov., from the Puno region in Peru is described, diagnosed and illustrated. An updated general description and distribution map of Bistriopelma are provided.